Il recupero del sé attraverso l'autobiografia - Trisciuzzi, Leonardo (Strumenti per la didattica e la ricerca, 2005)
An accurate definition of memory would embarrass any serious scholar. Briefly, memory could be defined as a wonderful mechanism, a way to transport us back in time. Memory is therefore a mental activity that binds us over time, it is what gives meaning to the existence. Self-narration or autobiography means first of all asking oneself about the status of one's own identity, it means communication, communicating to ourselves and to others who we are; it means transforming the interior monologue into dialogue with otherness; it means marking and regulating our emotions through the representation of the events of our life.